Evaluasi Tingkat Kepuasan Pasien terhadap Pelayanan Kesehatan Dasar di UPTD Puskesmas Batu Anam Kabupaten Simalungun - Dolorosa Margaretha Siregar; Acin Murdiana Butar Butar (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Patient satisfaction refers to the degree of emotion felt by an individual, arising from an assessment of the quality of medical care received, compared to initial expectations. Suspected dissatisfaction among visitors to the Huta Padang Community Health Center, Asahan Regency, appears to be due to the inadequacy of the primary care facilities provided at the institution. Information gathering was conducted from July to August 2023. This analytical study aimed to measure patient satisfaction with essential health care at the Regional Technical Implementation Unit (UPTD) of the Huta Padang Community Health Center, Asahan Regency. The target group of the study included all polyclinic patients visiting the Saribudolok Community Health Center. Respondents were selected using a purposive sampling technique, with a total of 64 participants. The study findings were summarized through a frequency distribution table, followed by statistical data processing via a Chi-square test at a 95% significance level (α = 0.05). The analysis revealed a relationship between primary care quality and patient satisfaction, indicated by a p-value of 0.018. Therefore, it is recommended for Community Health Center leaders to actively improve the standards of assistance provided, for example by providing encouragement or incentives for staff to carry out their duties optimally, so that they can realize patient anticipation.